Shear Strength Behaviors of Tire Shred-Dune Sand Admixtures - Elmootassem, Ruba A. (2024)
A Master of Science thesis in Civil Engineering by Ruba A. Elmootassem entitled, “Shear Strength Behaviors of Tire Shred-Dune Sand Admixtures”, submitted in January 2024. Thesis advisor is Dr. Magdi El-Emam. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).